Bond Valence Sum Parameters for Analyzing Pyranopterin Tungsten Enzyme Structures - Jesse Lepluart; Martin L. Kirk (Molecules)
The determination of tungsten oxidation states and W–ligand bond lengths for pyranopterin tungsten enzymes can be negatively impacted by Fourier series termination effects and photodamage/photoreduction in the X-ray beam. As a result, a new set of bond valence sum (BVS) parameters have been derived from bond length data on W(+4) and W(+6) model compounds that were obtained from X-ray crystallography. These new W enzyme-specific BVS parameters have been used in the analysis of pyranopterin tungsten enzyme structural data. The results of this analysis indicate that there are potential issues with the enzyme crystal structures, including the number of ligating atoms to the tungsten atom, the W–ligand bond lengths, and the W oxidation state. We conclude that a BVS analysis of crystallographic and EXAFS structural data will help address these issues, and EXAFS should be more routinely employed in the determination of pyranopterin tungsten enzyme active site structures due to the increased accuracy of this technique for the determination of W–ligand bond distances.